PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020) - Raihan Fadhilla Kurnia; Marsono Marsono (Diponegoro Journal of Accounting, 2022)
This research aims to examine the influence of financial performance to corporate social responsibility disclosure with good corporate governance as moderacy. Independent variables in this research are liquidity, leverage, and profitability. Dependent variable in this research is corporate social responsibility disclosure. Moderation variable in this research is good corporate governance. This research uses secondary data obtained from annual report and financial statement of minning sector companies on the Indonesian Stock Exchange. The sampling method that used is purposive sampling method. The sample used is minning sector companies were listed on the Indonesian Stock Exchange from 2017-2020 based on predetermined criteria. The analysis method used multiple regression analysis with IBM SPSS 26 program. Result of this research shows that liquidity has a positive effect on corporate social responsibility disclosure, while leverage and profitability have no effect on corporate social responsibility disclosure. The result also shows that good corporate governance cannot moderate the effect of liquidity, leverage, and profitability on corporate social responsibility disclosure.